Alat Pendeteksi Ketepatan Penggunaan Masker Berbasis Arduino Menggunakan Bahasa Pemrograman Python - Nofiar, Andri; Muhammad Ridwan, (SATIN - Sains dan Teknologi Informasi, 2022)
In early March 2020, Indonesia experienced an outbreak of the virus known as Corona Disease 2019 or covid-19 and has been declared by the World Health Organization as a pandemic on March 9, 2020. To prevent the transmission of the virus, the use of masks is a solution that is considered effective and efficient enough to prevent the spread of the covid-19 virus. But the use of this mask is sometimes still an unusual thing among the public. Detection of the use of masks so far is only done manually through observation by officers and this has some limitations that cannot be done every time and every place. For this reason, researchers make a mask-using precision detection tool made using machine learning. Machine learning works to classify data in the form of images then matched with the image of the face that has been captured, after which the data is sent to arduino as an output. If the facial data is not masked then LCD, red LED and Buzzer will light up. This python program is able to detect mask wearers with an accuracy of 100% at a distance of 50 cm. These results indicate that the problem can be solved properly.